Postnatal weight loss and neurodevelopmental outcomes at age 3 years in extremely preterm infants: a cohort study - Kei Tamai; Naomi Matsumoto; Takashi Yorifuji; Akihito Takeuchi; Makoto Nakamura; Misao Kageyama (BMC, 2024)
Abstract Background Previous research has suggested a correlation between postnatal maximum weight loss (MWL) and both neonatal mortality and morbidities in extremely preterm infants. However, the relationship between MWL and neurodevelopmental outcomes remains underexplored. Methods In a single-center, retrospective cohort study at Okayama Medical Center, we evaluated data from extremely preterm infants admitted to the neonatal intensive care unit from 2010 to 2020. Infants who died within the first 10 days of life were excluded. MWL in the first 10 days was the main exposure, categorized into three groups: >15%, 5-15%, and < 5%. The primary outcome evaluated was the occurrence of death or neurodevelopmental impairment (NDI) at age 3 years, defined as developmental impairments (developmental quotient [DQ] < 85), cerebral palsy, hearing impairments, or visual impairments. Data analysis involved robust Poisson regression, adjusted for perinatal confounders, with a restricted cubic spline function to examine the dose-response relationship. We also conducted a sensitivity analysis using a DQ of < 70 to define developmental impairment. Results Among 135 infants assessed for neurodevelopmental outcomes, 40 were in the > 15% MWL group, 71 in the 5-15% group, and 24 in the < 5% group. Median gestational ages and birth weights were 25.9 weeks and 821 g for > 15% MWL; 26.1 weeks and 818 g for 5-15% MWL; and 26.0 weeks and 734 g for < 5% MWL. Compared with the 5-15% MWL group, the < 5% group exhibited a higher risk of death or NDI at age 3 years (62.8% vs. 80.8%, risk ratio [RR] 1.36, 95% confidence interval [CI] 1.04-1.79) and NDI alone (59.2% vs. 79.2%, RR 1.43, 95% CI 1.06-1.94). Furthermore, higher risks of developmental impairment were also noted in the > 15% (RR 1.32, 95% CI 1.00-1.75) and < 5% (RR 1.46, 95% CI 1.08-1.98) groups. These associations were confirmed by spline analyses. In contrast, the associations between MWL and neurodevelopmental outcomes using a DQ of < 70 were not apparent. Conclusions MWL within the first 10 days of life may be associated with increased risks of NDI and developmental impairments by age 3 years in extremely preterm infants.